Natural vs. anthropogenic metals for reconstructing the source-to-sink pathway (Naples Bay, eastern Tyrrhenian Sea) - Milia, Alfonsa; Buonocunto, Francesco Paolo; Mali, Matilda; Giandomenico, Santina; Leo, Antonella Di; Spada, Lucia; Ferraro, Luciana; Giordano, Laura (Frontiers in Earth Science, 2023)
The sediments grain size, nutrients, and metals contents are important tracers to reconstruct the origin of the contaminants and the pathway of the sediments from the source to the sink. This is particularly important in areas with high geological variability and a high demographic pressure. Geochemical and physical parameters of sediments were analysed along a transect from the coastline to 112 m water depth, with the objective of exploring the spatial variability of sediment contamination in the continental shelf of Naples Bay. The latter is characterized by a complex geological area and subject to river inflow from a highly industrialized area. The data have been analysed using the Principal component analysis (PCA), Hierarchical correlation Analysis (CA) and analysis of variance (ANOVA). In order to distinguish between natural and anthropogenic origin of contaminants and to construct the source-to-sink pathway, the relationship between geochemical and physical data and their distribution was examined, and the results were compared with published data collected onshore. Four distinct sectors with different association of metals, grain size and TOC have been recognized. I) Offshore Vesuvius Volcano the occurrence of coarse grained sediments, associated with As, Fe, Mn, and low TOC values, suggests a natural origin of the contaminant due to volcanic nature of the substrate; II) offshore the Sarno River the presence of Cr, Cd, Cu, Pb and Zn, associated to the high TOC content, suggest an anthropogenic origin for the contaminants; III) offshore Sorrento Peninsula the presence of As, Fe, Mn, and some gravel made up of pumice and bioclasts indicate a predominance of contaminants of natural origin; IV) finally, the distal part is not subjected to a primary terrestrial input. The origin and distribution of contaminants and nutrients allow us to identify the source to sink pathway of the sediments. In particular, the Sarno river accounts for one of the main contributing sources of anthropogenic contaminants due to the outflow of surrounding large industrial area. Metals contamination of anthropogenic origin and the organic matter in sediments decreased rapidly with distance from the coast highlighting the main deposition area close to the river discharge.